The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1155/2020/1941480
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Treatment with Fluvoxamine Decreases Nonmotor Symptoms and Dopamine Depletion in a Postnatal Stress Rat Model of Parkinson’s Disease

Abstract: Nonmotor symptoms (NMS) such as anxiety, depression, and cognitive deficits are frequently observed in Parkinson’s disease (PD) and precede the onset of motor symptoms by years. We have recently explored the short-term effects of Fluvoxamine, a selective serotonin reuptake inhibitor (SSRI) on dopaminergic neurons in a parkinsonian rat model. Here, we report the long-term effects of Fluvoxamine, on early-life stress-induced changes in the brain and behavior. We specifically evaluated the effects of Fluvoxamine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 100 publications
1
14
0
Order By: Relevance
“…The levels of corticosterone in the SCI group remained high until the end of the observation period but decreased temporarily on day twentyone post injury, essentially consistent with the change in depressive behaviors. Additionally, the serum corticosterone concentration in the SCI group was strongly correlated with depressive-like behaviors in the SPT and FST, in alignment with previous research in different chronic stress models [31][32][33] and research that shows that this could be reversed by body weight-supported treadmill training [34].…”
Section: Discussionsupporting
confidence: 88%
“…The levels of corticosterone in the SCI group remained high until the end of the observation period but decreased temporarily on day twentyone post injury, essentially consistent with the change in depressive behaviors. Additionally, the serum corticosterone concentration in the SCI group was strongly correlated with depressive-like behaviors in the SPT and FST, in alignment with previous research in different chronic stress models [31][32][33] and research that shows that this could be reversed by body weight-supported treadmill training [34].…”
Section: Discussionsupporting
confidence: 88%
“…The study concluded that animals that were exposed to stress had high plasma levels of corticosterone and malondialdehyde, an effect that was attenuated with treatment with Fluvoxamine. Also, this drug appeared to attenuate the vulnerability of dopaminergic neurons to stress and neurotoxic treatments, such as 6-hydroxydopamine (6-OHDA) [59]. Thus, this study suggests the connection between serotonin and the stress associated with PD.…”
Section: In Parkinson's Diseasementioning
confidence: 62%
“…A study showed that acute administration of fluvoxamine inhibits the basal firing rate of dopaminergic neurons in the ventral tegmental area of rats 17. However, it was interesting to find that long-term treatment with fluvoxamine may downregulate dopamine transporters and preserve dopaminergic innervation in the striatum 18. Therefore, the dopaminergic mechanism of fluvoxamine-associated rhabdomyolysis remains unclear.…”
Section: Discussionmentioning
confidence: 99%